Effect of Online Consumer Review toward Purchase Intention: A Case of Premium Cosmetics in Nepal - Pandey, Rachana; G.C., Puspa; Aryal, Sabin (Nepalese Journal of Finance, 2025)
This study examines the effect of online consumer review toward purchase intention in the context of premium cosmetics in Nepal. Purchase intention is the dependent variable. The selected independent variables are source credibility, review quality, review valance, product knowledge, and benefit gaining. The primary source of data is used to assess the opinions of the respondents regarding source credibility, review quality, review valance, product knowledge, benefit gaining, and purchase intention. The study is based on primary data of 100 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of online consumer review toward purchase intention: A case of premium cosmetics in Nepal. The study showed that source credibility has a positive impact on purchase intention. It indicates that trustable and credible source of information leads to increase in purchase intention. Similarly, review quality has a positive impact on purchase intention. It indicates that product’s completeness and adherence to quality standards leads to inverse in purchase intention. Likewise, review valance has a positive impact on purchase intention. It indicates that positivity contained about the products lead to increase in purchase intention. In addition, product knowledge has a positive impact on purchase intention. It indicates that better knowledge of the product lead to increase in purchase intention. Further, benefit gaining has a positive impact on purchase intention. It indicates that higher the benefit of the products, higher would be the purchase intention.